Proyecto de inversión para la producción y distribución de pasta de soya en la ciudad de Guayaquil - Lucero Cabrera, Cinthya Elizabeth (2009)
Do you know the benefits of soybean meal? Do you know how many things you can cook with it? We developed a project which uses the final product of the process when you get the oil of grains of dried soybeans, also known as soybean meal, which can be used to soy milk, soy meat , soy cheese (tofu), energy drinks (horchata soybean), soy crackers and much more. We want to distribute the product in the city of Guayaquil with a consumer education campaign that teach the benefits of efficient and multifunctional products, such as soybeans and various grains of our country such as quinoa and barley. The goals is a quality product and good price, that is like 91 cents, with own simple distribution system to the local wholesalers and supermarkets, wholesalers, so they are our direct customers, but we create ways to maintain contact with end consumers. What we are trying to do is implement a marketing campaign with an unidirectional method to maintain a link with our customers, through paper that will be with next to the product where we will share recipes, experiences, news, events, discounts and more. Average investment level ($ 12,000), recovery of investment in a year, a large capacity for growing and profits are quite competitive advantages of choosing the project Soybean Meal in Guayaquil.